PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) UNTUK MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL SUB POKOK BAHASAN SEGITIGA DAN SEGIEMPAT KELAS VII D SMP NEGERI 7 JEMBER TAHUN AJARAN 2012/2013 - Susanti, Meri Ismi; Hobri, H; Setiawan, Toto' Bara (Department of Mathematics Education , University of Jember, 2014)
Abstrack: This research type of this research is Classroom Actions Research which consist of two cycles, there are two class in each cycles. The data collection methods are interview, documentation, observation, and test. The purpose of this research is to reduce students’ mistake during solving problem in the triangle and quadrilateral topic. We will use Missouri Mathematics Project (MMP) learning model in each meetings. The subject of research is students of VII D class SMPN 7 Jember in academic year 2012/2013. The data we analys are teacher’s and students’ learning activities, the percentage of student’s mistake, and the effectivity of MMP. The result of research indicate that the result of learning activity increase of student’s activity of cycle I reach 82,4% and cycle II reach 92,0%. While the student’s mistakes of final test at cycle I reach 50,5% and cycle II 28,6%. So, the mode of teaching can increase student’s activity and decrease the student’s mistakes. Key Words: Missouri Mathematics Project, triangle and quadrilateral topic, students’ activities, percentage of student’s mistake